Higher-Order Vagueness : Whether Vague Predicates Lack Sharp Boundaries - Lahtivirta, Jere (My University, 2019)
This thesis examines phenomenon of vagueness. Almost all expressions in natural languages are claimed to be vague. Two defining features of vague expressions are borderline cases and lack of sharp boundaries. The lack of sharp boundaries and so called higher-order vagueness are the main topics in this thesis. First the text introduces a particular conception of the lack of sharp boundaries. It is then shown how the presented conception with some plausible assumptions leads to higher-order vagueness. Then it is examined how different theories of vagueness are able to deal with higher-order vagueness. Most of these theories try to account vagueness by generating more boundaries. It is shown that these theories have problems to accommodate the lack of sharp boundaries and higher-order vagueness. At least one of these theories seem to avoid sharp boundaries, but there are crucial problems with higher-order vagueness itself. These problems are scrutinized and their implications to the lack of sharp boundaries are examined. I conclude that the way taken by the presented theories cannot manage to avoid sharp boundaries completely. In order to avoid sharp boundaries, I present a more radical account of vagueness that claims that vague predicates are boundaryless; they have neither sharp nor fuzzy boundaries. I then argue against this account, and show that any plausible version of it will generate sharp boundaries. Since both fuzzy boundaries and the boundaryless approach do not avoid sharp boundaries, it is concluded that vague predicates have sharp boundaries somewhere.
Keywords: Fuzzy Boundaries, Higher-order-vagueness, Philosophical logic, Philosophy of language, Sharp boundaries, Sorites paradox, Vagueness